Epistemic warrant for categorizational activities and the development of controlled vocabularies - Martínez-Ávila, Daniel [UNESP]; Budd, John M. (Emerald, 2017)
Purpose: The purpose of this paper is to update and review the concept of warrant in Library and Information Science (LIS) and to introduce the concept of epistemic warrant from philosophy. Epistemic warrant can be used to assess the content of a work; and therefore, it can be a complement to existing warrants, such as literary warrant, in the development of controlled vocabularies. In this proposal, the authors aim to activate a theoretical discussion on warrant in order to revise and improve the validity of the concept of warrant from the user and classifier context to the classificationist context. Design/methodology/approach: The authors have conducted an extensive literary review and close reading of the concept of warrant in LIS and knowledge organization in order to detect the different stances and gaps in which the concept of epistemic warrant might apply. The authors adopted an epistemological approach, in the vein of some of the previous commenters on warrant, such as Hope Olson and Birger Hjørland, and built upon the theoretical framework of different authors working with the concept of warrant outside knowledge organization, such as Alvin Plantinga and Alvin Goldman. Findings: There are some authors and critics in the literature that have voiced for a more epistemological approach to warrant (in opposition to a predominantly ontological approach). In this sense, epistemic warrant would be an epistemological warrant and also a step forward toward pragmatism in a prominently empiricist context such as the justification of the inclusion of terms in a controlled vocabulary. Epistemic warrant can be used to complement literary warrant in the development of controlled vocabularies as well as in the classification of works. Originality/value: This paper presents an exhaustive update and revision of the concept of warrant, analyzing, systematizing, and reviewing the different warrants discussed in the LIS literary warrant in a critical way. The concept of epistemic warrant for categorizational activities is introduced to the LIS field for the first time. This paper, and the proposal of epistemic warrant, has the potential to contribute to the theoretical and practical discussions on the development of controlled vocabularies and assessment of the content of works.
Keywords: Categorization; Epistemic warrant; Epistemology; Knowledge organization; Literary warrant; Warrant